Effect of fertilizer and water deficiency stress on nitrogen in the root mass yield of lucerne for seeds - Vasileva V. (Sustainable Mediterranean grasslands and their multi-functions, 2008)
A pot trial was carried out to determine the effect of fertilizer and water deficiency stress on nitrogen in the root mass yield of lucerne for seeds. Ammonium nitrate and well matured cattle manure, as a source of mineral and organic nitrogen, were used. The plants were grown under optimum moistening conditions (75-80% of field capacity) and water deficiency stress (37-40% of field capacity). Under optimum moisture conditions the use of mineral fertilizer at a dose of 210 and 70 mg N/kg soil increased nitrogen in the root mass yield by 9 and 21%, and the manure applied at the same doses by 36 and 43%. Under water deficiency stress conditions the use of mineral fertilizer decreased nitrogen in the root mass yield by 8 and 12%, and the manure application increased it by 24 and 28%. As a whole, water deficiency stress decreased nitrogen in the root mass yield by 26 and 35% under mineral fertilizer, and by 20-21% under manure application. Plants treated with manure are less susceptible to the stress conditions of water deficiency.
12. Meeting of the Sub-Network on Mediterranean Forage Resources of the FAO-CIHEAM Inter-regional Cooperative Research and Development Network on Pastures and Fodder Crop, 2008/04/09-12, Elvas (Portugal)